Pengembangan Media Pembelajaran Berbasis Video Tutorial “Fresh Make Up Look” Pengantin Pria pada Mata Kuliah Pengantin Internasional - Mediefa Ayu Raraendra Eday Tetha; Nurul Hidayah; Titin Supiani (Journal on Education, 2024)
Video tutorials as learning media can improve learning accuracy because students can see the learning process visually so that they can better understand the material delivered. This research is a type of research Research and Development (R & D) using a 4D development model namely Define, Design, Develop, and Disseminate. This development research is through a process of validation testing by the Materials Expert, Data Analysis Engineering using a mix of methods, where the collection and analysis of data is carried out with a combination of quantitative and qualitative research. The total score obtained from the Material Expert validation test at stage I and stage II was 77,5% where the presentation falls into the category "Worthy". Thus the video tutorial “Fresh Make up Look” Bride can be used as a learning medium on the International Bride Makeup Course.